The Sports Historian
The Sports Historian promotes the serious study of sport in society. Articles should deal with the economic, political, social, legal or philosophical significance of sporting activity. Whilst most articles in the past have been on British sport and have had an historical focus, articles on other societies and on contemporary sport may be submitted for consideration